Interpersonal Communication Model of Islamic Religious Counseling in the Community - Hasyim, Muhammad Yunus; Poernomo, Marlinda Irwanti (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
Interpersonal communication of Islamic religious instructors in the community plays an important role in conveying religious teachings and moral values to the community. This type of research includes descriptive qualitative research. To obtain data in the field, researchers use observation methods, interviews, and documentation. While in the subject in this study, how the effectiveness of the use of interpersonal communication of Islamic religious instructors to the community. The results of this study indicate that the success of this communication depends on the ability of instructors to manage the elements of interpersonal communication. Interpersonal communication that does not take place properly causes many obstacles to arise. Communication that is built without interest and no direct Interaction can eliminate the main factors in interpersonal communication. While the inhibiting factors in interpersonal communication between religious instructors and the community are as follows: interference factors in communication are physical, psychological, and semantic.